Post partum diastasis of the pubic symphysis: a case report - Pedrazzini, A.; Bisaschi, R.; Borzoni, et al., R. (Acta Biomedica Atenei Parmensis, 2005)
The post partum pubic symphysis diastasis is an uncommon disease. It is resposible of acute pelvic pain. It increases when manual pressure is applied to the pelvis in a latero-lateral and antero-posterior direction. The diagnostic test for this condition is an anteroposterior X-ray of the pelvis.Here we present a case following spontaneous vaginal delivery. The conservative treatment is able to obtain good results. If this disease is underestimated the patient can develop chronic pain.